Histological observations on precystic merogony and metrocyte formation of Sarcocystis rauschorum (Apicomplexa: Sarcocystidae) in varying lemmings, Dicrostonyx richardsoni - Cawthorn, Richard J.; Brooks, Ronald J. (Canadian Journal of Zoology, 1985)
This study was designed to elucidate the early endogenous development of Sarcocystis rauschorum (Apicomplexa: Sarcocystidae) in varying lemmings, Dicrostonyx richardsoni. After determining the dose–response effects of sporocysts of S. rauschorum on lemmings (doses greater than 500 sporocysts were lethal during hepatic merogony), sporocysts were administered to additional lemmings that were killed beginning 1 day postinoculation (DPI) and continuing to 15.0 DPI. Merogony of S. rauschorum occurs in hepatocytes 4 – 6 DPI; merozoites were also found in leucocytes 5 – 6 DPI in liver impression smears. Cyst formation began 9.0 DPI in striated muscle (rarely in cardiac muscle) and only metrocytes were present to 15.0 DPI. Overall, S. rauschorum has only one precystic generation of merogony, in hepatocytes, and then rapidly forms cysts containing metrocytes in striated musculature.